The Greener, the Higher: Labor Demand of Automotive Firms during the Green Transformation - Thomas Fackler; Oliver Falck; Moritz Goldbeck; Fabian Hans; Annina Hering (CESifo GmbH, 2024)
We investigate differences in labor demand between German automotive firms specializing in green propulsion technology and those with a focus on combustion engines. To this end, we introduce a firm-level labor demand index based on the near-universe of online job postings and firms' patent portfolios. Workforce adjustments are a crucial dimension of technology-related structural change, and labor demand as a highly reactive decision parameter is an ideal measure to detect employment adjustments. Our index enables us to distinguish labor demand by firms' greenness in real-time, a notable advantage over survey or administrative data. In a difference-in-differences setup, we exploit the poly-crisis triggered by unexpected escalations of trade conflicts and sustained by consequences of the pandemic and the war in Ukraine. We find green firms' labor demand is significantly and persistently higher than before the outbreak of the poly-crisis, by 34 to 50 percentage points compared to firms with a focus on combustion technology. This gap widens over time and is not driven by unobserved firm heterogeneity. Green firms systematically adjust labor demand towards production and information technology jobs.
Keywords: C55; J23; M51; O14; O33; 330; low carbon technology; firm employment decisions; sustainability; disruptive innovation